A construção da velhice positivada em propagandas televisivas direcionadas ao público idoso - Ribeiro, Raquel Noel (2007)
The present research inteded to study which positive positions circulate regarding the oldness in advertisement directed to the elderly audience, played by characters of this age group and transmitted on television. To discuss, from the social construccionism point of view, the oldness positivation construction in advertisements means to presuppose that those advertisements are not, fundamentally, only the result from the advertisers and comercial agencies work, but the result of its context of production: of the positivation discourse that circulates on an international and national levels concerning the oldness on a political, social, academic, economic and midiatic levels, the uses of these discourses and their consequences. Two recent television advertisements have been analysed Concurso Banco Real Talentos da Maturidade (6th edition), of 2004, and Se assim quiser, of 2005 that have as a common theme the positive oldness. The advertisements analyses went through three stages: 1) context of the advertisements production investigation; 2) description of each advertisement cene; 3) examination of the positive repertoires and of the maintainence of the stereotype conected to the aging process. The positive aspects, chosen to discuss how oldness is presented on the advertisements were: search of pleasure, personal satisfaction, autonomy (mental health), independence (physical health), diverse social roles, interests, income, entertainment, sociability, creativity and mobility. These interpretations alow the confirmation that the positivation on the two advertisements tend to be related to autonomy, independence, and income and exclude many people from those possibilities. Therefore the analyzed repertoires stimulate the folowing question: which are the experiencies of positivated oldness that people with illness and no financial resources can have?